2021
DOI: 10.1016/j.isci.2021.103212
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and prognostic value of LXR splice variants in triple-negative breast cancer

Abstract: Activity of liver x receptor (LXR), the homeostatic regulator of cholesterol metabolism, is elevated in triple-negative breast cancer (BCa) relative to other BCa subtypes, driving drug resistance and metastatic gene signatures. The loci encoding LXRa and LXRb produce multiple alternatively spliced proteins, but the true range of variants and their relevance to cancer remain poorly defined. Here, we report seven LXR splice variants, three of which have not previously been reported and five that were prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Thus, evaluating expression levels of both CLDN4 (input signal) and LXRβ (output signal) is required to predict distinct prognoses in TNBC cases. Along this line, clinicopathological analysis using expression levels of either CLDN4 [35][36][37] or LXRβ [51] does not seem to be enough to predict a prognosis in breast cancer, especially in TNBC. Since there is no valid medication for TNBC, it should also be worth noting that the CLDN4/LXRβ axis may be a promising therapeutic target for TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, evaluating expression levels of both CLDN4 (input signal) and LXRβ (output signal) is required to predict distinct prognoses in TNBC cases. Along this line, clinicopathological analysis using expression levels of either CLDN4 [35][36][37] or LXRβ [51] does not seem to be enough to predict a prognosis in breast cancer, especially in TNBC. Since there is no valid medication for TNBC, it should also be worth noting that the CLDN4/LXRβ axis may be a promising therapeutic target for TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, the truncated LXRs splice variants were observed to be associated with better prognosis in TNBC. They have reported 7 LXRs splice variants, in which 3 LXRs splice variants are newly reported such as LXRα4 (has different AF1 region), LXRα5 (lacks AF1 and LBD regions in greater level), and LXRβ1(has different AF1 region) respectively ( Lianto et al, 2021 ). GW3965 downregulates the transcription factor E2F2 expression, and reduces its attachment to the target genes (mostly cis regions), and also downregulates the genes involved in the proliferation, replication, and cell cycle in BC in vitro ( Nguyen-Vu et al, 2013 ).…”
Section: Lxrs In Cancermentioning
confidence: 99%
“…The activation of LXRs resists estrogen-induced cell proliferation by reducing estrogen receptor α at the mRNA and protein levels, but the exact mechanism remains to be further investigated [ 92 ]. Recently, a high expression of LXRs has been identified as a biomarker for a poor prognosis [ 93 , 94 , 95 ].…”
Section: Biological Functions and Mechanisms Of Lxrα In Diverse Cancersmentioning
confidence: 99%